Substituted tetracyclic indole core derivatives of HCV NS5A inhibitor MK-8742. Issue 19 (1st October 2016) - Yu, Wensheng; Zhou, Guowei; Coburn, Craig A.; Zeng, Qingbei; Tong, Ling; Dwyer, Michael P.; Hu, Bin; Zhong, Bin; Hao, Jinglai; Ji, Tao; Zan, Shuai; Chen, Lei; et al.
Graphical abstract: Abstract: As part of an ongoing effort in NS5A inhibition at Merck we now describe our efforts for introducing substitution around the tetracyclic indole core of MK-8742. Fluoro substitution on the core combined with the fluoro substitutions on the proline ring improved the potency against GT1a Y93H significantly. However, no improvement on GT2b potency was achieved. Limiting the fluoro substitution to C-1 of the tetracyclic indole core had a positive impact on the potency against the resistance associated variants, such as GT1a Y93H and GT2b, and the PK profile as well. Compounds, such as62, with reduced potency shifts between wild type GT1a to GT2b, GT1a Y93H, and GT1a L31V were identified.